Educationin healthon DST/Aids with adolescentsofa public school, usingtheeducational technologyas instrument - Camilo, Valesca Mara de B.; Freitas, Francisca Lidiane S.; Cunha, Valéria M.; Castro, Renata Kelly S. de; Sherlock, Maria do Socorro M.; Pinheiro, Patrícia Neyva da C.; Vieira, Neiva Francenely C. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: the infection by the human immunodeficiency virus (HIV) is growing among adolescents, whom are now seen as a group of high vulnerability to contamination. Objective: the study aimed to tell the experience of workshops about sexuality with adolescents using the educational technology as instrument; to investigate the knowledge, attitudes and practices regarding sexuality, contraception; to provide information on the main STD/aids, clearing doubts, myths and curiosities. Methods: descriptive and qualitative study, made in the 1st semester of 2007 with 26 students in the age group from 13 to 18 years in a state school in Fortaleza-CE. Results: the study revealed that the adolescents got involved in the activities without fear, participating actively of the activities. Conclusion: although most of the participants seek information about sexuality, their knowledge concerning STD/aids and contraception are inadequate, full of taboos. This way, therefore, it becomes indispensable the effective implementation of educational programs in schools, focusing on the prevention and the control of sexually transmitted diseases. The experience stimulated the teamwork and promoted the development of abilities related to actions in health education